2010
DOI: 10.1177/0734242x09360216
|View full text |Cite|
|
Sign up to set email alerts
|

Mass balances and life-cycle inventory for a garden waste windrow composting plant (Aarhus, Denmark)

Abstract: A comprehensive life-cycle inventory of all consumptions and emissions of environmental relevance was made for the windrow composting plant treating garden waste in Aarhus (Denmark). The flows of materials and substances within the facility were balanced using the mass-balance model STAN. The overall fuel and electricity use at the facility (3.04 L diesel Mg(-1) wet waste (ww) and 0.2 k Wh Mg(-1) ww) was low whereas the emissions of CH( 4) and N(2)O from the windrows (2.4 ± 0.5 kg CH( 4)-C Mg(-1) ww and 0.06 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Emissions of CH4, NH3 and N2O are modelled as a function of the degradation of Cand N-containing compounds. When possible, data regarding emissions should be gathered and modelled specifically for the assessed facility, as done for example in Andersen et al (2010)".…”
Section: Approach and Structurementioning
confidence: 99%
“…Emissions of CH4, NH3 and N2O are modelled as a function of the degradation of Cand N-containing compounds. When possible, data regarding emissions should be gathered and modelled specifically for the assessed facility, as done for example in Andersen et al (2010)".…”
Section: Approach and Structurementioning
confidence: 99%
“…Andersen et al (2010) found that 1.8 ± 0.9% of the total input N was lost as N 2 O emissions whereas Hellebrand (1998) measured that 1.7% of the initial N was lost as N 2 O and NH 3 , both in windrow composting of garden waste. N losses due to leachate and denitrification were however not quantified.…”
Section: Materials Flow Analysis For N and P In Bio-waste -Resultsmentioning
confidence: 97%
“…As for P, the loss via leachate is taken as 3% of the input P (Andersen et al, 2010). The nutrient content of compost is calculated by deducting the losses from the original N and P content in the green waste.…”
Section: Materials Flow Analysis For N and P In Bio-waste -Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case, uncertainty is expressed using a probabilistic framework by assuming the uncertain values to be normally distributed, that is, defined by mean values and standard deviations. The “normal approach” is included in this study because it is traditionally and widely used in MFA (e.g., Andersen et al ; Bonnin et al ; Dos Santos et al ; Ott and Rechberger ; Graedel et al ) and it has been implemented in the MFA software, STAN (cf. Cencic and Rechberger ), thereby providing a ready‐to‐use tool for including uncertainty in MFA.…”
Section: Introductionmentioning
confidence: 99%